MANAJEMEN BADAN USAHA MILIK DESA (BUMDES) - Sriayu Aritha Panggabean (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the management of BUMDes related to planning, organizing, implementing and supervising. This research uses a qualitative method of literature study by looking for authoritative literature from books and journals. The results showed that: 1) the ideal BUMDes planning can be done with collaborative planning based on deliberation. 2) the organization of BUMDes can be done by determining the right person in carrying out duties, it can be in the form of advisors, daily operational administrators and supervisors. 3) The implementation of BUMDes is the stage where planning and organizing are carried out as well as possible. 4) the supervision of BUMDes must go through three stages, namely setting standards, conducting assessments and carrying out corrective actions. Keywords: Management , BUMDes